Molecular genetic determinants of stress urinary incontinence in women: Prospective comparative study - Anna A. Mikhelson; Evgenia V. Lugovykh; Maria V. Lazukina; Tatiana B. Tretyakova; Anatoly N. Varaksin; Ekaterina D. Konstantinova (IP Berlin A.V., 2023)
Aim. To identify the molecular genetic determinants of stress urinary incontinence (UI) in women. Materials and methods. A comparative study involving 120 women was conducted. Group 1 (main group) included 80 women with UI. Group 2 (comparison group) included 40 women without UI. Statistic data processing was performed using the Excel software package, SPP Statistics 22.0, Statistica for Windows 10 (TIBCO Software Inc., Palo Alto, CA, USA). The mean and standard deviation were reported for quantitative variables with a normal distribution. The statistical hypotheses on the absence of intergroup differences for quantitative variables with normal distribution were verified using Student's test. The absolute and relative values (in percent) were reported for qualitative variables. The chi-square test was used to verify the statistical hypotheses. Results. Molecular genetic predictors of UI in women are the carriage of polymorphisms of the estrogen receptor gene ESR1:-351_G and the type I collagen gene COL1A1:1546_T. These polymorphisms can be considered as genotypes of "risk" since their carriage is associated with an increased risk of UI. Conclusion. Genetically determined disorders of the estrogen receptor function and type I collagen synthesis can be one of the essential mechanisms of stress incontinence occurrence. Studying molecular genetic determinants of stress incontinence can provide a deeper understanding of its pathogenetic mechanisms and develop a personalized approach to surgical correction.